Epstein–Barr virus-positive inflammatory follicular dendritic cell sarcoma of the liver: A case report - Jong-Shiaw Jin; Kuan-Chun Hsueh; Cheng-Chun Lee; Tang-Yi Tsao; Hong-Wei Gao (Tungs’ Medical Journal)
A 59-year-old female presented with a 1-year history of epigastric pain, vomiting, and acid regurgitation. Initial evaluation indicated peptic ulcer disease, and subsequent imaging identified a liver mass. Histopathological analysis confirmed an Epstein–Barr virus-positive inflammatory follicular dendritic cell sarcoma. This case report discusses the clinical presentation, diagnostic challenges, differential diagnoses, and surgical management of this rare neoplasm, along with a review of similar cases in the literature.